Systemic Inflammatory Response and Adhesion Molecules - L. V. Molchanova (Общая реаниматология)
The lecture presents the materials of foreign studies on the mechanisms responsible for the formation of a systemic inflammatory response syndrome (SIRS). The hypotheses accounting for the occurrence of SIRS in emergencies are described. Adhesion molecules (AM) and endothelial dysfunction are apparent to be involved in the inflammatory process, no matter what the causes of SIRS are. The current classification of AM and adhesion cascades with altered blood flow is presented. There are two lines in the studies of AM. One line is to measure the concentration of AM in the plasma of patients with emergencies of various etiology. The other is to study the impact of antiadhesion therapy on the alleviation of the severity of terminal state and its outcome. The studies provide evidence for that an adhesive process is a peculiar prelude to a systemic inflammatory response.